Great Noses Are Blown Alike : Zakdoekenpocket. - Lemmens, Oriana; Broeckaert, Colette (S.l. : Posture Editions, 2023)
Aernoudt, Celine ; Apers, Jonas ; Auwers, Stan ; Buysse, Leonie ; Clappaertn Stefan ; D'haene, Olga ; Sneeze Ensemble, De Clerck, Lukas ; De Mulder, Krista ; De Vos, Kasper ; Decraene, Laurence ; Degraeve, Louise ; Demeulenaere, Hans ; Demoen, Gustave ; Demoen, Nikolaas ; Diepens, Carina ; Durinck, Dieter ; Herman, Gerard ; Herman, Judith ; Leye, Veva ; Libens, Oona ; Meulenijzer, Amber ; Meulenijzer, Patrick ; Pauwels, Ruben ; Peeters, Dries ; Raciti, Elisa ; Rombouts, Guy ; van Campenhout, Ad ; Van den Broucke, Jakob ; Van Laer, Pomme ; Van Laethem, Dries ; Vandenbroucke, Charlotte ; Vanhee, Klaas ; Vantorre, Lisa
Les Mouchoirs de Poche, Convent space for contemporary art, Ghent, (01.12.2023-17.12.2023) ; Museum of Industry, Ghent, (17.01.2024-14.02.2024)
boek